THE FOUNTAIN FITNESS PARK - Revana, Ayu; Hendriana, Hendriana; Widjaja, Stephen; Angkasa, Josef Darmawan (Bina Nusantara University, 2013)
In major cities, people started to feel bored with the daily routine activities and also a traffic jam, three aspects of the loss of the consequences of congestion which are: fuel wastage due to the vehicle operating cost 3 Billion IDR, losses due to the time wasted 2.5 Billion IDR, and the health impacts of air pollution 2.8 Billion IDR.